Terahertz emission from localized modes in one-dimensional disordered systems [Invited] - Zeng, Yongquan (2021)
We demonstrate terahertz (THz) frequency laser emission around 3.2 THz from localized modes in one-dimensional disordered grating systems. The disordered structures are patterned on top of the double-metal waveguide of a THz quantum cascade laser. Multiple emission peaks are observed within a frequency range corresponding to the bandgap of a periodic counterpart with no disorder, indicating the presence of mode localization aided by Bragg scattering. Simulations and experimental measurements provide strong evidence for the spatial localization of the THz laser modes.